Evaluation of Sepsis/Systemic Inflammatory Response Syndrome, Acute Kidney Injury, and RIFLE Criteria in Two Tertiary Hospital Intensive Care Units in Turkey - TUĞLULAR, ZÜBEYDE SERHAN (KARGER, 2010)
Sepsis is a common cause of acute renal failure in intensive care units (ICU) with mortality rates as high as 60%. In this study, the clinical and laboratory predictors of acute kidney injury (AKI) in critically ill Turkish patients with sepsis/systemic inflammatory response syndrome were identified. We studied 139 (67 females/72 males) patients admitted to our ICUs with sepsis/systemic inflammatory response syndrome without renal failure. The clinical and laboratory parameters and treatments were recorded. Patients were classified as those without AKI (n = 60; 43.20%) and those with AKI (n = 79; 56.80%) based on the RIFLE (Risk, Injury, Failure, Loss, End-stage renal disease) criteria. Those with AKI were further classified as: risk in 27 (19%), injury in 25 (17.9%), failure in 25 (17.9%), and loss in 2 (1.4%). We found that the mortality rate increased with the severity of renal involvement: 56% in risk, 68% in injury, 72% in failure, and 100% in loss categories. Patients with AKI had a more positive fluid balance, higher central venous pressure, more vasopressor use, and lower systolic blood pressure. In multivariate analysis, the sequential organ failure assessment score, blood pressure, serum creatinine, and fluid balance were risk factors for the development of AKI. In this population, the incidence of AKI was higher and contrary to previous knowledge. A positive fluid balance also carries a risk for AKI and mortality in septic ICU patients. The RIFLE criteria were found to be applicable to our ICU population. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Acute renal failure; RIFLE criteria; Sepsis/systemic inflammatory response syndrome; ACUTE-RENAL-FAILURE; CRITICALLY-ILL; FLUID BALANCE; SYNDROME SIRS; MORTALITY; DIURETICS; SEPSIS; MULTICENTER; DISEASE; ARF